Enhanced transformability with heterospecific deoxyribonucleic acid in a Streptococcus sanguis mutant impaired in ribonucleic acid polymerase activity. - Raina, J L (1976)
We have induced with nitrosoguanidine in Streptococcus sanguis a mutation conferring inability to grow and synthesize ribonucleic acid (RNA) at 42 C, the optimal temperature for growth and RNA synthesis in the parental strain. The mutation (ts) is transferable via transforming deoxyribonucleic acid (DNA) and is replaceable by its wild-type allele with fairly high efficiency in transformation reactions. The ts mutation is unlinked to the sites of mutation conferring resistance of rifampin (rifr) and streptolydigin (stgr), known to affect the beta subunit of DNA-dependent RNA polymerase. Extracts from strains carrying the ts mutation are more sensitive to elevated temperatures than are parental extracts when assayed for DNA-dependent RNA polymerase. The conclusion that the mutation causes a temperature-sensitive defect in some component of this enzyme (other than beta) is supported by the finding that the polymerase activity of a heat-inactivated ts stgr extract cannot be increased by addition of an unheated ts stgs extract, which is itself inactivated by streptolydigin. S. sanguis recipients carrying the ts mutation are highly transformable with heterospecific DNA, especially at the restrictive temperature.